( Identification of soil associations with the aid of radar images). - Garcia, G. J.; Espindola, C. R.; Galhego, H. R. (My University, 1983)
This study used semicontrolled radar mosaics in the scale 1:250 000. The parameters used in this case were drainage indices as follows: drainage density, frequency of channels and texture ratio. Through statistical analysis was possible to select the main soil associations in each region, with a good accuracy. Due to scale, the level of details was lower than the level that could be obtained through panchromatic photographs. -from English summary
Utilizacao de imagens de radar na identificacao de solos sob cerrado.